Compact Uplink Circularly Polarized 2.4GHz Short Backfire Antenna for Geostationary Amateur Radio Satellite Es’Hail-2 (QO-100) - Michal Cerveny; Pavel Hazdra (IEEE Open Journal of Antennas and Propagation)
This paper describes a compact circularly polarized antenna designed for the 2.4GHz band with a gain of 15dBic designed for communication (uplink) with a geostationary amateur radio satellite Es’Hail-2 (QO-100). The proposed antenna upgrades a standard short backfire antenna (SBA) by utilizing two metasurfaces with the first acting as a high-impedance surface (HIS) allowing for a reduction of the distance between the sub-reflector and main reflector and the second enhancing the sub-reflector while functioning both as a tunable polarization divider and phase shifter to form the circular polarization. This novel concept enables the use of a simple, linearly polarized patch antenna as a feeder with no complex feeding networks. The proposed antenna was simulated, manufactured, measured and tested with the QO-100 transponder located on the Es’Hail-2 geostationary satellite. This antenna is suitable for situations where compactness, portability, a rigid construction, and a simple change of direction of the circular polarization are required.